Recent insights on epidemiology, diagnosis and control of Classical and African Swine Fever in pig industry - Rai, Sajana (Journal of Agriculture and Natural Resources, 2024)
Classical swine fever is caused by an enveloped RNA virus in the genus Pestivirus of the family Flaviviridae, whereas African swine fever (ASF) is caused by a double-stranded DNA virus in the genus Asfivirus of the family Asfarviridae. Both diseases are devastating and cause great loss in the pig industry through mortality, growth retardation, and poor reproductive performance. The clinical symptoms of African swine fever and classical swine fever in pigs can be extremely similar; hence laboratory testing is necessary to distinguish between both diseases. Virus isolation, fluorescent antibody test (FAT), antigen capture antibody enzyme-linked immunosorbent assay (ELISA), reverse-transcription polymerase chain reaction (RT-PCR), virus neutralization test (VNT), and antibody ELISA have been developed for diagnosis of CSF. For detection of ASF, ELISA, chemiluminescent immunoassay (CLIA), PCR, luciferase immunoprecipitation assay (MB-LIPS), loop-mediated isothermal amplification (LAMP), and recombinase polymerase amplification (RPA) have been developed. For the piggery business to grow, quick diagnosis and effective preventative measures are needed to aid in the management and elimination of both diseases. Pigs have been protected against these diseases through vaccination. Preventing entry of the CSF and ASF viruses through strict quarantine measures is necessary. Early detection and knowledge of the disease's epidemiology are crucial for both preventing the disease's spread and developing an effective management strategy. This review provides insights on the etiological agent, epidemiology, transmission mode, clinical symptoms, pathogenesis, diagnosis, and control strategies of both diseases.